“La lúdica y animación en el proyecto posada de juguetes de la carrera de Educación Inicial” - Bautista Ronquillo, Tania Elizabeth (2023)
This research focuses on, "Playful and animation at the Posada de Juguetes project from the nursery major" for satisfying socio-cultural needs, achieving participation among students, teachers, parents and children, given the problem evidenced in the scarcity of animation techniques applied by the participants from Posada de Juguetes, where this objective is proposed: "Diagnose the incidence of playfulness and animation at the Posada de Juguetes project from the nursery major", on the other hand, this research is a mixed approach, bibliographic and field modality, following the inductive method; the techniques applied are observation and interview with their respective instruments. The interview was addressed to the "Posada de Juguetes" project students and the survey was applied to the Fifth level from nursery major students. The results obtained determined, if play and animation have an impact on the Posada de Juguetes project, because by knowing and applying animation techniques, will allow them to better fulfill the planned activities, optimizing the students’ integration, intervention and participating in the Project among them.